2005
DOI: 10.1111/j.1751-1097.2005.tb00214.x
|View full text |Cite
|
Sign up to set email alerts
|

UV‐Mediated DNA Strand Breaks in Corneal Epithelial Cells Assessed Using the Comet Assay Procedure

Abstract: Ultraviolet (UV)‐mediated DNA damage in various tissues has been well documented. However, research on the damaging effect of UV irradiation on the DNA of corneal epithelium is scarce, even though this is of interest because the cornea is directly exposed to damaging solar (UV) radiation. In this study, we developed a corneal epithelium Comet assay model to to assess the background DNA damage (as strand breaks) n cells retrieved from different layers of the porcine corneal epithelium, and to investigated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…The most damaging, by a factor of almost two over UVA and UVC, was found to be UVB. 19 Such an assessment of DNA damage is likely to be a more sensitive test of the effect of UV on cells compared with the current study, where a less sensitive, but more clinically applicable live/dead staining technique was used. Again, putting this in context, a 1-s exposure to the UVC LED in the current study, with an output of 1.93mW/cm 2 , would equate to a dose of 1.93 mJ/cm 2 , and even the 30-s exposure would amount to only 57.95 mJ/cm 2 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The most damaging, by a factor of almost two over UVA and UVC, was found to be UVB. 19 Such an assessment of DNA damage is likely to be a more sensitive test of the effect of UV on cells compared with the current study, where a less sensitive, but more clinically applicable live/dead staining technique was used. Again, putting this in context, a 1-s exposure to the UVC LED in the current study, with an output of 1.93mW/cm 2 , would equate to a dose of 1.93 mJ/cm 2 , and even the 30-s exposure would amount to only 57.95 mJ/cm 2 .…”
Section: Discussionmentioning
confidence: 88%
“…Despite the considerable cumulative lifetime exposure of the cornea to both UVB and UVA, as well as to visible ambient light, a retrospective study by Lee and Hirst in 1992 reported an incidence of histologically proven dysplasia, carcinoma in situ, and invasive carcinoma of the cornea and conjunctiva of only 1.9 per 100 000 per year, averaged over a 10-year period. 21 Given the similarity in damage observed histologically for UVA and UVC, 19 it would seem unlikely that a short additional exposure to UVC would significantly increase the risk of carcinogenicity. 21 Naturally, the potential risk to ocular structures would depend, not only on the DNA-damaging potential of the light itself, but, also, on penetration to deeper structures.…”
Section: Discussionmentioning
confidence: 99%
“…Scant information is available regarding types and levels of DNA damage in the corneal epithelium in the human eye. A gradient of DNA damage has been described in the corneal epithelium in animal eyes where levels of DNA strand breaks were observed to decrease from the surface towards the basal layer (Choy et al 2005). Levels of DNA strand breaks and levels of oxidized bases are generally very low in the epithelium on human donor corneas maintained in cold storage.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in levels of strand breaks and also in levels of oxidized bases in the epithelium may be observed after transfer of the donor corneas to organ culture ). Environmental stressors such as UV-irradiation and airborne particulate matter have been shown to induce DNA strand breaks in cultivated human and animal epithelial cells (Choy et al 2005;Gao et al 2016). Unrepaired, such damage may act to destabilize cell function through an increased level of transcriptional errors (Ishibashi et al 2005).…”
Section: Discussionmentioning
confidence: 99%